2022
DOI: 10.3390/cancers15010140
|View full text |Cite
|
Sign up to set email alerts
|

Blood Plasma Metabolome Profiling at Different Stages of Renal Cell Carcinoma

Abstract: Early diagnostics significantly improves the survival of patients with renal cell carcinoma (RCC), which is the prevailing type of adult kidney cancer. However, the absence of clinically obvious symptoms and effective screening strategies at the early stages result to disease progression and survival rate reducing. The study was focused on revealing of potential low molecular biomarkers for early-stage RCC. The untargeted direct injection mass spectrometry-based metabolite profiling of blood plasma samples fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 74 publications
1
5
0
Order By: Relevance
“…In this study, the entire amino acid pathway was found to be downregulated, aligning with previous findings [6,16,46]. RCC subtypes exhibited significant changes in amino acid metabolism and redox homeostasis [46].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the entire amino acid pathway was found to be downregulated, aligning with previous findings [6,16,46]. RCC subtypes exhibited significant changes in amino acid metabolism and redox homeostasis [46].…”
Section: Discussionsupporting
confidence: 91%
“…To the best of our knowledge, 13 prior case-control studies have identified potential metabolic biomarkers in plasma [6][7][8][9][10] or serum [11][12][13][14][15][16][17][18] that distinguish RCC from controls. The proposed profiles include lipids, lipoproteins [6][7][8][9][13][14][15]17,18], amino acids [6][7][8]10,[12][13][14]17], and carbohydrates [7,11,13,14,16]. However, robust RCC diagnostic biomarkers remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Among the top causes of death worldwide, cardiovascular disease and cancer constitute about nearly half of global deaths. 1 Atrial fibrillation (AF) is the most prevalent sustained arrhythmia worldwide and a well‐known factor in cardiovascular morbimortality. 2 , 3 Besides, AF patients are also confronted with a substantial risk of mortality from non‐cardiovascular causes.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical treatment is the preferred option for managing renal carcinoma, while immunotherapies have shown sensitivity instead of chemotherapy drugs ( Klapper et al, 2008 ; Aggen et al, 2021 ). Currently, the prognosis of targeted drugs that combined to inhibit angiogenesis is unsatisfactory ( Maslov et al, 2022 ; Li et al, 2023 ). Previous studies have shown that renal carcinoma is a malignant tumor that relies on angiogenesis and hypoxia.…”
Section: Introductionmentioning
confidence: 99%